2015
DOI: 10.3340/jkns.2015.58.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Repeated Head CT Necessary for All Pediatric Traumatic Brain Injury?

Abstract: ObjectiveRepeated computed tomography (CT) follow up for traumatic brain injury (TBI) patients is often performed. But there is debate the indication for repeated CT scans, especially in pediatric patients. Purpose of our study is to find risk factors of progression on repeated CT and delayed surgical intervention based on the repeated head CT.MethodsBetween March, 2007 and December, 2013, 269 pediatric patients (age 0-18 years) had admitted to our hospital for head trauma. Patients were classified into 8 subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
2
15
1
Order By: Relevance
“…When the causes are categorised according to age subgroups: falls are common in infants, whereas road accidents are more common in older children, respectively [ 1 ]. Male predominance in pediatric age head traumas was reported in multiple series as same as the present study (males-53%, p = 0.002) [ 1 , 9 , 13 - 16 ]. This finding could be explained by the risk-taking behaviour of boys [ 1 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…When the causes are categorised according to age subgroups: falls are common in infants, whereas road accidents are more common in older children, respectively [ 1 ]. Male predominance in pediatric age head traumas was reported in multiple series as same as the present study (males-53%, p = 0.002) [ 1 , 9 , 13 - 16 ]. This finding could be explained by the risk-taking behaviour of boys [ 1 ].…”
Section: Discussionsupporting
confidence: 83%
“…What the rate of follow-up CT scans in our study was 11.8%, which is far behind the rates of similar studies (24-65%) [ 9 , 24 ]. Repeat CT scan resulted in late surgical intervention in only one patient (1%), which is comparable to other similar studies (1-24%) [ 8 , 9 , 11 , 25 , 26 , 28 ]. Kim et al, found only the epidural hematoma other than another kind of intracranial pathologies being a predictor of late surgical intervention.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…It is also known as progressive hemorrhagic injury. 5,6,7,8,9,10 CT scan modality is used for quick assessment of acute head trauma and informs management of the patients. It informs the surgeon if the patient required decompressive surgery or conservative monitoring.…”
Section: Introductionmentioning
confidence: 99%